2016
DOI: 10.7759/cureus.639
|View full text |Cite
|
Sign up to set email alerts
|

Extensive Bone Marrow Necrosis and Osteolytic Lesions in a Case of Acute Myeloid Leukemia Transformed from Polycythemia Vera

Abstract: Acute myeloid leukemia (AML) is the most common leukemia in adults. In rare cases, bone marrow necrosis (BMN) and osteolytic lesions are presenting features of AML. The following case describes a patient with known polycythemia vera (PV) that presented with signs of multiple myeloma, including hypercalcemia, anemia, and lytic lesions of the thoracic spine and skull. Laboratory workup was not indicative of myeloma. A bone marrow biopsy was performed, which revealed extensive BMN and initial pathology was consis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 10 publications
0
23
0
Order By: Relevance
“…Hypercalcemia, which occurs in multiple myeloma, lymphoma, or any other solid tumor, is usually related to the disease itself, but in PV, it is usually due to other causes such as primary hyperparathyroidism, due to adenoma or carcinoma, or due to other solid malignancies. Also, it has been reported that hypercalcemia is associated with PV transformation into acute myeloid leukemia [6]. Although there are case reports and studies that describe an association between hypercalcemia and PV, most of them are old, from a time at which the PV diagnosis was unclear, and it was established before introducing the WHO criteria in 2008 [7].…”
Section: Discussionmentioning
confidence: 99%
“…Hypercalcemia, which occurs in multiple myeloma, lymphoma, or any other solid tumor, is usually related to the disease itself, but in PV, it is usually due to other causes such as primary hyperparathyroidism, due to adenoma or carcinoma, or due to other solid malignancies. Also, it has been reported that hypercalcemia is associated with PV transformation into acute myeloid leukemia [6]. Although there are case reports and studies that describe an association between hypercalcemia and PV, most of them are old, from a time at which the PV diagnosis was unclear, and it was established before introducing the WHO criteria in 2008 [7].…”
Section: Discussionmentioning
confidence: 99%
“…4,9 AML is the most common leukemia in adult humans. 10 Clinical presentation of AML is diverse and non-specific. 11 It is often associated with cytopenias and may include fatigue, hemorrhage, infection, pallor, and dyspnea.…”
Section: A S E Rep Ortmentioning
confidence: 99%
“…11 There have been rare reports of AML in humans associated with bone marrow necrosis and osteolytic lesions as seen in this baboon. 10 Adverse prognostic indicators in humans include age over 60 years, white blood cell count…”
Section: A S E Rep Ortmentioning
confidence: 99%
“…BMN is a histopathologic diagnosis characterized by destruction of the medullary stroma with preservation of cortical bone. Severe BMN occurs in about 2.4% of AML [5]. The overall survival of AML with BMN is 3.7 months compared to 14 months in those without BMN [6].…”
Section: Introductionmentioning
confidence: 99%